Risk of infection following semi-invasive ultrasound procedures in Scotland, 2010 to 2016: A retrospective cohort study using linked national datasets. (August 2018) - Scott, David; Fletcher, Eilidh; Kane, Hayley; Malcolm, William; Kavanagh, Kimberley; Banks, A-Lan; Rankin, Annette
Introduction: Outbreak reports indicate a risk of cross-infection following medical procedures using semi-invasive ultrasound probes. This study aimed to evaluate the risk of infection, using microbiological reports and antibiotic prescriptions as proxy measures, associated with semi-invasive ultrasound probe procedures, including transoesophageal echocardiography, transvaginal and transrectal ultrasound. Methods: Patient records from the Electronic Communication of Surveillance in Scotland and the Prescribing Information System were linked with the Scottish Morbidity Records for cases in Scotland between 2010 and 2016. Three retrospective cohorts were created to include inpatients/day-cases and outpatients in the following specialties: Cardiology, Gynaecology and Urology. Cox regression was used to quantify the association between semi-invasive ultrasound probe procedures and the risk of positive microbiological reports and community antibiotic prescriptions in the 30-day period following the procedure. Results: There was a greater hazard ratio of microbiological reports for patients who had undergone transoesophageal echocardiography (HR: 4.92; 95% CI: 3.17–7.63), transvaginal (HR: 1.41; 95% CI: 1.21–1.64) and transrectal ultrasound (HR: 3.40; 95% CI: 2.90–3.99), compared with unexposed cohort members after adjustment for age, co-morbidities, previous hospital admissions and past care home residence. Similarly, there was a greater hazard ratio of antibiotic prescribing for those who had received transvaginal (HR: 1.26; 95% CI: 1.20–1.32) and transrectal (HR: 1.75; 95% CI: 1.66–1.84) ultrasound, compared with unexposed patients. Conclusion: Analysis of linked national datasets demonstrated a greater risk of infection within 30 days of undergoing semi-invasive ultrasound probe procedures, using microbiological reports and antibiotic prescriptions as proxy measures of infection.